Evaluation of The Development of Critical Life Skills as A Result of Participating in Texas Youth Horse Judging Programs - Dibbs, Ashley; Zoller, Jennifer; Huseman, Chelsie; Cummings, Scott (Journal of extension, 2025)
Competitive judging teams are valued forms of extracurricular learning tools for many youth students. Unfortunately, unless individuals have direct involvement in these programs the benefits often go unnoticed and undocumented. A survey was designed to assess self-perceived life skill development from current and past horse judging participants, as well as youth life skill development observed by adults. Participants identified critical thinking, decision making, and public speaking as the highest rated life skills developed. Adults ranked self confidence, critical thinking and decision making as the skills they observe develop most frequently.